PENERAPAN SENAM OTAK (BRAIN GYM) DALAM MENINGKATKAN KONSENTRASI PADA ANAK USIA PRASKEOLAH (4-6 TAHUN) DI KB IFFAT KOTA JAMBI - Oktaria, Rina; Djelita, Adila Puspa; Simorangkir, Apni Riama (Jurnal Ilmu-Ilmu Kesehatan, 2024)
The preschool age is a golden period in the process development. This period includes a sensitive period or sensitive period in children, for that children need to learn with high concentration, because of the consequences of the lack of concentration of children, the learning outcomes are not optimal. The purpose tihis study is find out the effectiveness of applying brain gymas management in increasing concentration in young children preschool 4-6 years. This type of research is descriptive with a case study method one subject group consists of 2 people for 3 days. Measurement using a questionnaire and then observed before and after carrying out the technique brain gym. The results obtained in this study obtained increased results in the value of concentration after doing brain exercises for 3 times the implementation of gymnastics brain. Before the brain exercise is carried out, the concentration value of An.M is 6 and after carrying out brain exercises for 3 times the concentration value of An. M increases to 15. While in An.H before carrying out value brain exercises An.H concentration is 5 and after doing brain exercises 3 times the concentration value of An. H increases to 10. This proves that the application of brain gymnastics can improve concentration in children. The conclusion is applying brain gym it can be proven increase concentration in children with a decrease in concentration in iffat KB Jambi in 2023. It is hoped that brain exercises can be applied by the iffat in the KB overcome concentration problems in children.Keywords : Brain Gym, Concentration, Preeschol